Ensayos de calidad ambiental de un ladrillo de construcción, obtenido a partir de mezclas que incluyen relaves de flotación de minerales polimetálicos - Pardavé Livia, Walter (2022)
This work deals with environmental quality tests applied to a construction product made with mixtures that include polymetallic mineral flotation tailings. The tests that were performed to the solid brick and the mining tailings with treatment, are based on Resolution 0631 of 2015 chapter 5, which establishes the parameters and maximum permissible limit values in point discharges to surface water bodies and public sewage systems, our brick will be exposed to the outdoors therefore when it rains, the water drains by runoff to the sewage system. In the present work we evaluate each of the following parameters: pH, CONDUCTIVITY (µS/cm), RESISTANCE (25°C) (MΩ-cm), TDS PPM (Total dissolved solids), TEMPERATURE (°C), ORP (mV), PHOSPHATES (mEq/L), NITRATES NO3- (ppm), NITRITES (NO2-) (ppm), HEAVY METALS (mEq/L). The results obtained and compared with Resolution 631 of 2015 show us that the tests performed on the brick chips are optimal and comply with the established limits, i.e. they can be used in construction.